Investigating the Assessment Procedures for Children With Complex Communication Needs - Theodorou, Elena; Pampoulou, Eliada (My University, 2022)
Successful intervention outcomes and comprehensive assessment is important, for people who rely on augmentative and alternative communication (AAC). However, the literature surrounding AAC assessment remains sparse. The purposes of this project were to describe the AAC assessment process followed by speech and language pathologists (SLPs) and to suggest areas for a comprehensive assessment. The research questions are (a) to identify the training received and (b) to explore the key elements of the assessment process. A questionnaire was developed based on the Participation Model and completed by 89 SLPs. The findings show that SLPs base their AAC assessment on clinical decisions, taking into consideration a number of elements, such as language, communication, and social skills. However, the process uncovered through this research cannot be characterized neither comprehensive nor systematic. The findings indicate that further training on AAC assessment is warranted, thus ensuring high quality of services for people with complex communication needs.
Keywords: Assessment; Augmentative and alternative communication; Complex communication needs; Speech and language pathologists